Investigating inflammatory bowel disease–white cell scanning, radiology, and colonoscopy. Issue 1 (January 1996) - Jobling, J C; Lindley, K J; Yousef, Y; Gordon, I; Milla, P J
Abstract : OBJECTIVE: To evaluate different methods of examination of the bowel in suspected inflammatory bowel disease. DESIGN: Prospective investigation of all children over a three year period with suspected inflammatory bowel disease. A technetium-99m-HMPAO labelled white cell scan (Tc-WCS), barium follow through examination (Ba-FT), and colonoscopy plus biopsy were undertaken. SETTING: Great Ormond Street Hospital for Children, London. SUBJECTS: 39 children (20 male and 19 female), median age 12.1 years (range 3.9-15.1 years). MAIN OUTCOME MEASURES: There was total agreement in 21/39 cases, positive in 16, and negative in five. Of 31 histologically proved cases, positive results were obtained in 28 Tc-WCSs (sensitivity 90%), 10 of 24 Ba-FTs (sensitivity 42%), and 27 colonoscopies (sensitivity 87%). CONCLUSION: The Tc-WCS is sensitive, specific, and non-invasive and should be a first line investigation. Ba-FT with a high radiation burden and relatively low sensitivity requires its role to be redefined. Colonoscopy, with endoscopic biopsy, has a high pick-up rate where facilities and expertise exist.